2013
DOI: 10.2135/cropsci2012.10.0603
|View full text |Cite
|
Sign up to set email alerts
|

Yield Potential of Hulless Versus Hulled Full‐Sib Genotypes in Four Winter Barley Populations

Abstract: Determining what factors contribute to the yield difference that exists between hulled and hulless winter barley (Hordeum vulgare L.) is necessary for continued yield improvement in the hulless barley germplasm pool. This yield difference is a major factor limiting the acceptance and production of hulless barley as an alternative to traditional hulled barley. Experiments were conducted in Warsaw, VA, during 2010/2011 and 2011/2012 and in Blacksburg, VA, during 2011/2012. Seedling emergence, plants per square m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…On average, hulled lines (excluding checks) yielded 6458 kg ha -1 , whereas, on average, hull-less lines yielded 6353 kg ha -1 , a difference of only 105 kg ha -1 . In a multi-location study comparing differences in yield potential between hulled and hull-less full-sib genotypes, Berger et al (2013) found no significant differences between hulled and hullless lines when adjustments were made for the hull weight lost during threshing. Alba, which is a high-yielding feed variety, had a significant yield advantage over all experimental lines (Table 2).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…On average, hulled lines (excluding checks) yielded 6458 kg ha -1 , whereas, on average, hull-less lines yielded 6353 kg ha -1 , a difference of only 105 kg ha -1 . In a multi-location study comparing differences in yield potential between hulled and hull-less full-sib genotypes, Berger et al (2013) found no significant differences between hulled and hullless lines when adjustments were made for the hull weight lost during threshing. Alba, which is a high-yielding feed variety, had a significant yield advantage over all experimental lines (Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…When the yield of Alba is adjusted for hull (7266 kg ha -1 ), the comparison with the average of the hull-less lines (6353 kg ha -1 ) is more favorable. In a multi-location study comparing differences in yield potential between hulled and hull-less full-sib genotypes, Berger et al (2013) found no significant differences between hulled and hullless lines when adjustments were made for the hull weight lost during threshing. This supports our conclusions that hull-less lines have the potential to compete with hulled lines when the hull weight is taken into consideration.…”
Section: Resultsmentioning
confidence: 97%